Microbiome profiles of non-responding and responding paired periodontitis sites within the same participants following non-surgical treatment. Issue 1 (31st December 2022) - Byrne, SJ; Chang, D; Adams, GG; Butler, CA; Reynolds, EC; Darby, IB; Dashper, SG
ABSTRACT: Aim: Periodontitis is a site-specific, chronic disease treated by non-surgical debridement of subgingival plaque. We aimed to determine the microbiome of sites that did not respond to this treatment (NR) compared with paired good responding (GR) sites before and after treatment. Materials and methods: In a longitudinal cohort study, clinical parameters of disease and biological samples were taken prior to and 3 months after treatment. Twelve NR sites from six participants were paired with GR sites within the same participant. Subgingival plaque samples were subjected to bacterial community analysis using 16S rRNA gene sequencing. Results: There were no significant differences in clinical parameters and microbial communities at baseline between GR and NR sites. Bacterial communities in deep pockets were dominated by a small number of species, notably Porphyromonas gingivalis and Treponema denticola . In NR sites three months after treatment there was no significant change in bacterial composition whilst there was a collapse in the abundance of pathobionts in GR sites. Conclusion: NR sites were not identifiable prior to treatment by clinical or microbiological parameters. Treatment failed to disrupt pathogenic bacterial community in NR sites. Targeted suppression of particular species should be considered to initiate community collapse and aid disease resolution.